Pengaruh Pembelajaran Daring Masa Pandemi Covid 19 Terhadap Hasil Belajar Siswa Di Madrasah Ibtidaiyah Miftahul Ulum Desa Watestanjung Wringinanom Gresik - Khusnan, Ach; Wahyudi, Muhammad Irfan (FATAWA: Jurnal Pendidikan Agama Islam, 2021)
The purpose of this study (1) to determine the implementation of online learning in Madrasah Ibtidaiyah Miftahul Ulum, Watestanjung Wringinanom Gresik (2) To determine the effect of online learning on student learning outcomes at Madrasah Ibtidaiyah Miftahul Ulum, Watestanjung Wringinanom Gresik village. In line with the research objectives, this research is quantitative with a descriptive approach. The research subject is class VI, which consists of 26 students. Methods of data collection using interviews (interviews), questionnaires (questionnaire), and documentation. The technique of examining research instruments, data analysis is quantitative with the aim of testing the established hypothesis. The results of the study: (1) The implementation of online learning at Madrasah Ibtidaiyah Miftahul Ulum Watestanjung Wringinanom Gresik was less effective because there were many obstacles faced by teachers, parents/guardians and students during online learning of moral aqidah subjects when students were given assignments (2) From the results The output of SPSS Coefficients of Simple Linear Regression has a t count of 0.587 with a specified significance level of 5% = 0.05 and a degree of freedom of 26 in the t table of 1.706. The calculated t value = 0.587 is smaller than the t table value of 1.706, so Ho is accepted. then Ho is accepted, because Ho is accepted so there is no influence between X and Y.